Felt embodiment as a motive in flourishing - Lundh, Lars-Gunnar; Foster, Lo (Frontiers in Psychology, 2025)
As individual persons, we are all embodied in the sense that we have a body with certain needs, sensory systems, feelings, and capacities. Humans and some other animals also have an experience of embodiment, defined as an experience of “my body.” This is a combined experience of having a body (the body as an object that can be perceived, imagined, thought about, and evaluated according to different standards) and being this body (the subjective experience of the felt body). The latter is not about the body as an object but is focused on how the body feels. The main claims of the present paper are (1) that we have a need to feel embodied, and that this is important for the development of self-identity, interpersonal relations, wellbeing, and flourishing in general; and (2) that experiences of feeling embodied can serve as important motives, both in a positive sense (embodiment motivation) and a negative sense (disembodiment motivation). In the present paper, felt embodiment motivation is illustrated by the motivation to feel one’s body (1) in its vitality and capacities, both in rest and in movement (e.g., physical activity and dancing), and in its expressiveness; (2) as being an integrated part of wholesome environments, and (3) in pleasurable and loving bodily contact with significant others. Disembodiment motivation is defined as the motive to avoid or reduce bodily self-experiences, for example due to physical or emotional pain or other forms of bodily discomfort. In brief, the present paper outlines a new area of research: embodiment motivation, defined as the motivation to feel one’s own body, its vitality, capacities, and expressiveness, its embeddedness in wholesome environments, and the embodied contact with others, and its opposite: disembodiment motivation.